Criminalização operativa: travestis e normas de gênero - Júlia Silva Vidal (2020)
This paper aimed to understand how the criminalization of transvestites materializes and what is its relation to gender norms. Unveiling the mechanisms and weavings that make up the legal and illegal dimensions that produce this criminalization is central to this work. To this end, I started from my ethnographic experience as a lawyer and an activist with transvestites, field notebook records and analysis of criminal proceedings in order to elaborate scenes. With the restitution of the camp, I proposed to start meetings and to circumvent the articulation movement that produces the criminalization of transvestites. Considering that prostitution, migration, precariousness, institutional violence, pathologization, alternative measures to imprisonment, among others, intertwine the networks that produce the criminalization of transvestites, I concluded that crime, far from being an abstract entity, is only effective because it is anchored in processes located in each place, produced in each act, triggered by multiple actors and supported by gender norms. In terms of criminalization and gender, i demonstrated the movements of assembling and disassembling to show how coherence is constructed in the articulatory practices of heterogeneous elements constituting a truth in operation in the acts. Finally, i defended operative criminalization as a theoretical and methodological approach that allows us to realize that the organization, distinction and distribution of offenses - as well as their character of truthfulness - are the result of the articulation of a multifaceted series of mechanisms and actors of extension and varied character.